2019
DOI: 10.1097/sla.0000000000003395
|View full text |Cite|
|
Sign up to set email alerts
|

Decreasing Trends in Intestinal Resection and Re-Resection in Crohn's Disease

Abstract: Objective: To assess time trends in intestinal resection and re-resection in Crohn's disease (CD) patients. Summary of Background Data: CD treatment has changed considerably over the past decades. The effect of these advances on the necessity of intestinal resections and the risk of re-resection is unclear. Methods: In this nationwide cohort study, adult CD patients with ileocolonic, small bowel, colon, or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Studies from Denmark 12,13 , Manitoba 8 , UK primary care 14 and the Netherlands 15 have all reported decreasing rates of intestinal resection for CD over time. The Dutch group even noted decreasing surgical rates for all anatomical locations and repeat resections during the entire period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from Denmark 12,13 , Manitoba 8 , UK primary care 14 and the Netherlands 15 have all reported decreasing rates of intestinal resection for CD over time. The Dutch group even noted decreasing surgical rates for all anatomical locations and repeat resections during the entire period.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch group even noted decreasing surgical rates for all anatomical locations and repeat resections during the entire period. Of note, the incidence of surgery was, however, based on an estimated, rather than known prevalence of CD in the Netherlands 15 . Other studies have reported conflicting data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite the difference in the source of data between both studies (Canada: health administrative data and the Netherlands: nationwide pathology database), a declining rate of intestinal resections in Crohn's disease has been confirmed in Canada, at equal rates as the decline that has been observed in the Netherlands. 2 The authors used an advanced statistical method to analyse the impact of anti-TNFα introduction on (among other end points) the rate of intestinal resection. However, in our opinion, the hypothesised direct relationship between introduction of anti-TNFα and a decline in intestinal resection rate is vastly oversimplified for two important reasons.…”
mentioning
confidence: 99%
“… 1 Despite the difference in the source of data between both studies (Canada: health administrative data and the Netherlands: nationwide pathology database), a declining rate of intestinal resections in Crohn’s disease has been confirmed in Canada, at equal rates as the decline that has been observed in the Netherlands. 2 …”
mentioning
confidence: 99%